2004
DOI: 10.1021/la036465v
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Arrangements of Polystyrene Latex Particles with a Hyperbolic Quadruple Electrode System

Abstract: An attempt was made to arrange polystyrene latex particles (2, 5, and 10 microm in diameter) dispersed in aqueous media making use of their dielectrophoresis and electrophoresis with a hyperbolic quadruple electrode system. Application of a high-frequency ac field enabled the particles to arrange themselves between the electrodes forming a particle monolayer due to the negative dielectrophoretic force. Simultaneous application of high-frequency ac and dc fields caused the particles to gather in the region surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…Negative DEP force at high frequency in hyperbolic quadrupolar electrodes with a non-uniform gap enforced the concentration of microspheres, thus allowing colloidal crystal domains at the center of the electrodes [41]. In our study, similar experiments were conducted using hexapolarshaped electrodes embedded in a microfluidic chamber, as shown in Fig.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Negative DEP force at high frequency in hyperbolic quadrupolar electrodes with a non-uniform gap enforced the concentration of microspheres, thus allowing colloidal crystal domains at the center of the electrodes [41]. In our study, similar experiments were conducted using hexapolarshaped electrodes embedded in a microfluidic chamber, as shown in Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Recently, dielectrophoretic assembly of colloidal microspheres has been reported as a rapid and convenient method to construct 2D colloidal crystals [10,36,41]. Negative DEP force at high frequency in hyperbolic quadrupolar electrodes with a non-uniform gap enforced the concentration of microspheres, thus allowing colloidal crystal domains at the center of the electrodes [41].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its ability to handle cells or particles without any modification of them, it has become one of the most attractive manipulation techniques in a microfluidic device or a lab-on-a-chip. In recent studies, many research groups have revealed the dielectric properties of polystyrene microbeads (Abe et al 2004;Choi and Park 2005), DNA (Lao and Hsing 2005), bacteria (Li and Bashir 2002;Lagally et al 2005), yeast (Perch-Nielsen et al 2003;Doh and Cho 2005), leukocytes (Wang et al 2000), and erythrocytes (Minerick et al 2003). The dielectrophoretic force is described as follows:…”
Section: Introductionmentioning
confidence: 99%